The Analysis of Gerunds in The Adventure of Sherlock Holmes - Khalid Fattah El Hakim; Sri Widodo; Ismawati Ike Nugraeni (Scripta : English Department Journal, 2021)
Abstract. This research aims are to identify the uses of gerunds found in The Adventure of Sherlock Holmes and to describe their application in teaching reading. It belongs to qualitative research. The researchers used a collection of short stories by Arthur Conan Doyle entitled The Adventure of Sherlock Holmes as the data source. The researchers then identified the sentences containing gerund, classified the gerund found in the short story based on its use, counted the percentage of the gerunds, discussed the finding of the analysis, applied the result of finding in teaching reading, and drew conclusion and suggestion. In conclusion, there are 2 gerunds as subject (0.71%), 13 gerunds as direct object (4.59%), and 268 gerunds as object of preposition (94.70%) and they can be applied in teaching reading for the twelfth-grade students of Language Program of senior high school.